Expected product market reforms and technology adoption by Senegalese onion producers - Bernard, Tanguy; de Janvry, Alain; Mbaye, Samba; Sadoulet, Elisabeth (Wiley, 2017)
We assess the responsiveness of Senegalese onion producers to their knowledge of expected changes in product market conditions, whereby onions would no longer be sold based on volume but rather on weight and with labeling certifying quality. A village‐level randomized information campaign on the upcoming introduction of these reforms induced significant investments by farmers into quality‐enhancing inputs. Delays in the actual introduction of scales enabled us to rigorously identify positive price effects from these investments. Our results point to the importance of farmers’ expectations regarding the improved functioning of product markets in triggering technology adoption.